Impact of Information Presentation Format on Preference for Total Knee Replacement Surgery. Issue 3 (28th February 2019) - Fraenkel, Liana; Benjamin Nowell, W.; Stake, Christine E.; Venkatachalam, Shilpa; Eyler, Rachel; Michel, George; Peters, Ellen
Abstract : Objective: Patients have a poor understanding of outcomes related to total knee replacement (TKR) surgery, with most patients underestimating the potential benefits and overestimating the risk of complications. In this study, we sought to compare the impacts of descriptive information alone or in combination with an icon array, experience condition (images), or spinner on participants' preference for TKR. Methods: A total of 648 members of an online arthritis network were randomized to 1 of 4 outcome presentation formats: numeric only, numeric with an icon array, numeric with a set of 50 images, or numeric with a functional spinner. Preferences for TKR were measured before and immediately after viewing the outcome information using an 11‐point numeric rating scale. Knowledge was assessed by asking participants to report the frequency of each outcome. Results: Participants randomized to the icon array, images, and spinner had stronger preferences for TKR (after controlling for baseline preferences) compared to those viewing the numeric only format ( P < 0.05 for all mean differences). Knowledge scores were highest in participants randomized to the icon array; however, knowledge did not mediate the association between format and change in preference for TKR. Conclusion: Decision support at the point‐of‐care is being increasingly recognized as a vital component of care. Our findings suggest that adding graphic information to descriptive statistics strengthens preferences for TKR. Although experience formats using images may be too complex to use in clinical practice, icon arrays and spinners may be a viable and easily adaptable decision aid to support communication of probabilistic information.